Assessing the Macroeconomic Impact of Structural Reforms in Chile - Hadzi-Vaskov, Metodij (IMF Working Papers; Working Paper ;, 2018)
This study investigates the likely macroeconomic impact of various structural reforms that align the Chilean regulatory framework with international best practices. In this context, the analysis: i) presents a comparison across a large set of structural indicators; ii) identifies policy gaps with respect to OECD countries; and iii) provides quantification of the likely growth and fiscal impact of policy reforms needed to close the gaps. Chile's economy is likely to benefit from streamlining business regulation and licensing, strengthening innovation and R and D capacity, improving labor market flexibility, and enhancing active labor market policies. Overall, the study presents a scenario in which Chile closes structural gaps with OECD's 25th percentile over five years, with up to 6 percent higher output level and a cumulative net fiscal gain of about 1\2 percent of GDP.